2020
DOI: 10.3389/fnins.2020.577119
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Anaesthetic Protocols and Management as Confounders in Rodent Blood Oxygen Level Dependent Functional Magnetic Resonance Imaging (BOLD fMRI)–Part A: Effects of Changes in Physiological Parameters

Abstract: Background: To understand brain function in health and disease, functional magnetic resonance imaging (fMRI) is widely used in rodent models. Because animals need to be immobilised for image acquisition, fMRI is commonly performed under anaesthesia. The choice of anaesthetic protocols and may affect fMRI readouts, either directly or via changing physiological balance, and thereby threaten the scientific validity of fMRI in rodents. Methods: The present study systematically reviewed the literature investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…Results of the systematic search, including a PRISMA flow chart as well as detailed results of the risk of bias assessment of all included studies, are reported in part a of the review [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of the systematic search, including a PRISMA flow chart as well as detailed results of the risk of bias assessment of all included studies, are reported in part a of the review [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…An overview which anesthetics have been compared for stimulation and rsfMRI in rats and mice is given in Figure 3 , and in more detail in Supplementary Materials Table S1 , where for each reference it is listed which anesthetics were investigated. Studies which exclusively compared dose-dependence or time-dependence for two anesthetics are covered in previous sections, and results of studies which investigated effects of physiological parameter changes are covered in part a of this review [ 15 ]. Differences between anesthetics were found in all except three datasets (baseline BOLD signal after blood withdrawal, isoflurane versus halothane versus propofol [ 57 ]; response to peripheral electrical stimulation, medetomidine versus α-chloralose [ 50 ]; rsfMRI, isoflurane versus ketamine/xylazine [ 58 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations